Evaluation of Shredded Duri Lele Sanitation Standard Operating Procedure (SSOP) in UMKM XYZ - Zahrotul Chumairo; Alifia Rosida; Riski Ayu Anggreini; Diana Aqidatun Nisa (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Sanitary procedures play an important role in achieving food safety. The application of sanitation in the food industry has a standard procedure, namely the Sanitation Standard Operating Procedure (SSOP). SSOP is important to apply, not only in large industries but also in small and medium enterprises. XYZ UMKM is located in Mojokerto, East Java. This MSME is engaged in processed catfish. UMKM XYZ products in particular are shredded catfish meat and spines. There are problems related to sanitation in these MSMEs, such as the use of untested water for production, workers who do not understand the principles of sanitation, the layout of the storage room that is integrated with the production room, to the workers' sanitation facilities that are not properly maintained for cleanliness. This situation can be corrected by evaluating the SSOP in the production process which is the scope of this community service activity. The method of implementing this community service activity consists of internal coordination and coordination with partners, carrying out SSOP reviews by observation and through partner interviews, to evaluating the results of the review and Focus Group Discussion between teams and partners. Data analysis was carried out based on 8 key aspects of SSOP requirements. Observation results are described using tables and explained in narrative form. The implementation of SSOP in the scope of the production area and toilets at UMKM XYZ is in accordance or meets the SSOP of 57.57%. Other SSOP parameters need to be improved by improving the quality of sanitation, through the application of solutions provided according to SSOP, so it is hoped that this evaluation can guarantee quality and increase product competitiveness in the market.